Implementasi Fisioterapi Dada Pada Asuhan Keperawatan Dengan Bersihan Jalan Napas Tidak Efektif Pada Pasien Paru Obstruktif Kronik (PPOK) - Rizqi, Januar; Feoh, Desi Ardianti (JUKEJ : Jurnal Kesehatan Jompa, 2024)
Shortness of breath and excessive sputum production are signs of chronic obstructive pulmonary disease (COPD). Excess sputum production compromises airway patency. This study investigates the application of chest physiotherapy in the treatment of patients with Chronic Obstructive Pulmonary Disease (COPD), focusing on its impact on airway clearance and respiratory function. Chest physiotherapy includes techniques such as percussion, vibration, postural drainage, and breathing exercises designed to loosen and mobilize secretions, thereby improving airway clearance and enhancing respiratory function. Methods: This qualitative study was conducted in Anggrek Room of Muntilan Hospital, involving two COPD patients for six days. Data collection included patient assessment forms, effective cough implementation checklists, and observation formats for major and minor problems related to ineffective airway clearance. Results: the results showed that after three days of chest physiotherapy, one respondent (Respondent 1) showed minimal improvement in secretion clearance, while the other patient (Respondent 2) experienced effective secretion clearance. Conclusion: This study concludes that although chest physiotherapy is effective in improving airway and secretion clearance, continued research is essential to optimize its application and improve long-term patient outcomes.